Zombie Board: Board Tenure and Firm Performance - HUANG, Sterling (Institutional Knowledge at Singapore Management University, 2017)
We show that board tenure exhibits an inverted U-shaped relation with firm value and accounting performance. The quality of corporate decisions, such as M&A, financial reporting quality, and CEO compensation, also has a quadratic relation with board tenure. Our results are consistent with the interpretation that directors’ on-the-job learning improves firm value up to a threshold, at which point entrenchment dominates and firm performance suffers. To address endogeneity concerns, we use a sample of firms in which an outside director suffered a sudden death, and find that sudden deaths that move board tenure away from (toward) the empirically observed optimum level in the cross-section are associated with negative (positive) announcement returns. The quality of corporate decisions also follows an inverted U-shaped pattern in a sample of firms affected by the death of a director.